1990
DOI: 10.1161/01.hyp.15.6.659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NG-monomethyl-L-arginine and L-arginine on acetylcholine renal response.

Abstract: Intrarenal infusion of acetylcholine in meclofenamate-treated dogs significantly increased renal blood flow, diuresis, and natriuresis. Intrarenal infusions of either A^'-monomethyl-L-arginine (inhibitor of endothelium-derived relaxing factor formation), or L-arginine (precursor of endothelium-derived relaxing factor formation) did not modify basal levels of those parameters. However, the infusion of A^-monomethyl-L-arginine inhibited the acetylcholineinduced increases in renal blood flow and diuresis without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…3). PD ing 10 Addition of methylene blue (I0-M) alone to M-1 cultures had no significant effect on ISC (51±2 to 54±1 ,uA/cm2) or PD (-37±2 to -39±2 mV). Addition of Bk (10-9 M) to methylene blue-treated M-1 cells in the presence of CPAE cells also produced no significant effect on IS, (54±0.5 to 56±0.5 AA/ cm2) or PD (-40±1 to -39±1 mV).…”
Section: Resultsmentioning
confidence: 97%
“…3). PD ing 10 Addition of methylene blue (I0-M) alone to M-1 cultures had no significant effect on ISC (51±2 to 54±1 ,uA/cm2) or PD (-37±2 to -39±2 mV). Addition of Bk (10-9 M) to methylene blue-treated M-1 cells in the presence of CPAE cells also produced no significant effect on IS, (54±0.5 to 56±0.5 AA/ cm2) or PD (-40±1 to -39±1 mV).…”
Section: Resultsmentioning
confidence: 97%
“…Acetylcholine infusion has also been reported to have a diuretic and natriuretic effect (33,34). Lahera et al (35) reported that this acetylcholine-induced diuretic effect was dependent on intact NO synthase activity. Thus, in vivo experimental evidence suggests that stimulation of NO synthesis results not only in vasodilatation, but diuresis and natriuresis as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an important role for nitric oxide as an endothelial-derived relaxing factor in the regulation ofboth systemic and regional vascular resistances (2,3,15,17). This work was designed to assess the role ofnitrovasodilatation in the homeostasis of intrarenal oxygen supply to the renal medulla, a region normally operating on the verge of hypoxia (6) and therefore likely to have strong vasodilatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%